Use of Random Amplified Polymorphic DNA (RAPD) Technique to Study the Genetic Diversity of Eight Aloe Species - Ezzat, Shahira M.; El Sayed, Abeer M.; Salama, Maha M. (Planta Medica, 2016)
The genus Aloe comprises over 400 species of flowering succulent plants. Aloe leaves are used in the treatment of asthma, gastrointestinal ulcers, cardiovascular disease, tumors, burns, and diabetes. They are rich in anthraquinones, such as aloin, aloe-emodin, chrysophanol, aloinoside A, and aloinoside B. The various species of Aloe show chemical and morphological similarity and diversity, which depend on the genotype and environmental conditions. In a continuity to our interest in the genus Aloe, this study targets the authentication of eight different Aloe species, Aloe vera (A1), Aloe arborescens (A2), Aloe eru (A3), Aloe grandidentata (A4), Aloe perfoliata (A5), Aloe brevifolia (A6), Aloe saponaria (A7), and Aloe ferox (A8), grown in Egypt by using the technique of random amplified polymorphic DNA. Twelve decamer primers were screened in amplification with genomic DNA extracted from all species, of which five primers yielded species-specific reproducible bands. Out of 156 loci detected, the polymorphic, monomorphic, and unique loci were 107, 26, and 23, respectively. Based on a dendrogram and similarity matrix, the eight Aloe species were differentiated from each other and showed more divergence. Aloe species prevailed similarity coefficients of 54–70 % by which they could be classified into three major groups. Thus, this technique may contribute to the identification of these Aloe species that have great morphological similarity in the Egyptian local markets.
Keywords: Aloe species; Xanthorrhoeaceae; authentication; DNA markers; clustering